Managing chemically deteriorated soils of India - Goswami, R. G.; Bajpai, R. K. (Indian Farming, 2018)
Chemical deterioration of soils is a type of soil degradation that involves loss of nutrients or organic matter, salinization, acidification, soil pollution and fertility decline. The removal of nutrients reduces the capacity of soils to support plant growth and crop production and causes acidification. In arid and semi-arid areas problems can arise due to accumulation of salts, which impedes the entry of water in plant roots. Chemical deterioration of soils is often also due to agricultural over exploitation, relying solely on replenishing nutrient losses through harvesting by artificial chemical fertilizers. Indiscriminate irrigation for getting higher yield has led to waterlogging; nutrient losses and increased salinization of lands threatened the sustainability of crop yields. The increasing salinization of thousands of hectares of cultivated lands with raised watertable in many canal command areas is a serious threat and needs attention failing which a significant area may be rendered unproductive and unfit for cultivation.